The mechanistic study of codonopsis pilosula on laryngeal squamous cell carcinoma based on network pharmacology and experimental validation - Guo, Huina; Lou, Yichen; Hou, Xiaofang; Guan, Xiaoya; Guo, Yujia; Han, Qi; Xue, Xuting; Wang, Ying; He, Long; Li, Zhongxun; Zhang, Chunming (Frontiers in Pharmacology, 2025)
IntroductionLaryngeal squamous cell carcinoma (LSCC) is a common malignant tumor of the head and neck, with poor prognosis for advanced patients, and there is an urgent need to find new treatment strategies. Codonopsis pilosula, a traditional Chinese medicinal herb, possesses various pharmacological activities, but its antitumor effects and mechanisms in LSCC are still unclear. The aim of this study was to systematically investigate the potential antitumor mechanism of Codonopsis pilosula in LSCC.MethodsIn this study, we screened the effective compounds and targets of Codonopsis pilosula by TCMSP, ETCM and BATMAN-TCM databases, and screened targets related to LSCC by combining DisGeNET, GeneCards database and Cytoscape software. KEGG pathway enrichment analysis was utilized to explore the related signaling pathways. The core targets were further screened based on TCGA and GEO database analysis, and molecular docking was carried out to predict their binding ability to effective compounds. The presence of key compounds was verified by LC-MS, the MAPK3 expression was detected by qPCR in LSCC tissues, and the effects of MAPK3 knockdown on proliferation, migration, invasion, cell cycle, and apoptosis of LSCC cells were evaluated by cellular function assays.ResultsIn this study, 22 targets of Codonopsis pilosula that might regulate LSCC were screened based on network pharmacology. KEGG pathway enrichment analysis showed that Codonopsis pilosula-LSCC targets were mainly involved in HIF-1, TNF, IL-17 and FoxO signaling pathways. Based on TCGA and GEO database analysis, MAPK3 was identified as the core target of Codonopsis pilosula-LSCC. The molecular docking results showed that a variety of effective compounds from Codonopsis pilosula had strong binding abilities to MAPK3, among them, Caprylic Acid, Emodin and Luteolin have been confirmed by LC-MS. QPCR analysis indicated that MAPK3 was highly expressed in LSCC tissues. MAPK3 knockdown significantly inhibits LSCC cell proliferation, migration and invasion. It also suppresses LSCC cell growth by blocking the cell cycle and inducing apoptosis.ConclusionCodonopsis pilosula exerts antitumor effects in LSCC through the regulation of MAPK3 and multiple signaling pathways, providing a theoretical basis for its clinical application.